Biomarkers Affected by Impact Severity during Osteochondral Injury - Waters, Nicole Poythress; Stoker, Aaron M.; Pfeiffer, Ferris M.; Cook, James L. (The Journal of Knee Surgery, 2015)
Osteochondral injury elevates the risk for developing posttraumatic osteoarthritis (PTOA). Therefore, our objective was to evaluate the relationship between impact severity during injury to cell viability and biomarkers possibly involved in PTOA. Osteochondral explants (6 mm, n = 72) were harvested from cadaveric femoral condyles (N = 6). Using a test machine, each explant (except for No Impact) was subjected to mechanical impact at a velocity of 100 mm/s to 0.25, 0.5, 0.75, 1.0, or 1.25 mm maximum compression corresponding to Low, Low-Moderate, Moderate, Moderate-High, or High impact groups. Cartilage cell viability, collagen content, and proteoglycan content were assessed at either day 0 or after 12 days of culture. Culture media were assessed for prostaglandin E2 (PGE2); nitric oxide; granulocyte macrophage colony-stimulating factor (GM-CSF); interferon gamma (IFNγ); interleukin (IL)-2, -4, -6, -7, -8, -10, -15, -18; interferon gamma-induced protein 10 (IP-10); keratinocyte-derived chemoattractant (KC); monocyte chemoattractant protein-1 (MCP-1); tumor necrosis factor alpha (TNFα); and matrix metalloproteinase-2, -3, -8, -9, -13. There was increased impact energy absorbed for the High group compared with the Moderate-High group, Moderate group, and Low-Moderate group (p = 0.011, 0.048, 0.008, respectively). At day 0, there was decreased area cell viability for the High group compared with the Low-Moderate group (p = 0.035). At day 1, PGE2 was increased for the High group compared with the Moderate, Low-Moderate, Low, and No Impact groups (p ≤ 0.01). Cumulative PGE2 was increased for the Moderate-High and High groups compared with the Moderate, Low-Moderate, Low, and No Impact groups (p ≤ 0.036). At day 1, MCP-1 was increased for the Moderate-High and High groups compared with the Low and No Impact groups (p ≤ 0.032). Impact to osteochondral explants resulted in multiple levels of severity. PGE2 was sensitive to impact severity which may justify its use as a clinically measurable biomarker after joint injury for monitoring early PTOA.
Keywords: cartilage injury; biomechanics; cell death; prostaglandin E2; biomarkers